1995
DOI: 10.1007/bf01256704
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography in pneumatosis intestinalis: Differential diagnosis and therapeutic consequences

Abstract: Case reports of five patients with pneumatosis intestinalis diagnosed by computed tomography (CT) are presented. Etiology, differential diagnoses, and clinical consequences arising from CT imaging are discussed. In four of the patients, pneumatosis was found to be secondary to gastric ulcer, colon carcinoma, metastasis in the mesentery, and trauma-induced mesenteric ischemia. In one patient, the etiology remained elusive. Using CT, both the extent and the distribution pattern of pneumatosis could be depicted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 34 publications
0
22
0
3
Order By: Relevance
“…After intestinal perforation has been radiologically excluded, conservative treatment 13 of PCI is advisable including parenteral nutrition and a diet of low-flatulenceproducing carbohydrates. In cases of concomitant infection appropriate antimicrobial therapy is beneficial in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…After intestinal perforation has been radiologically excluded, conservative treatment 13 of PCI is advisable including parenteral nutrition and a diet of low-flatulenceproducing carbohydrates. In cases of concomitant infection appropriate antimicrobial therapy is beneficial in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the primary type, PCI is usually located in the submucosal layer of the left hemicolon or its mesentery, and the intramural gas collections are a spherical, well-defined cystic appearance. In the secondary type, PCI is usually limited to the subserosal layer of the stomach, small intestine and right colon, and intramural gas may appear as curvilinear lucencies that circumscribe a loop of the bowel when observed en face and parallel to a long segment when seen lengthwise (4,7). It is widely accepted that abdominal radiographs and CT can demonstrate the intraluminal gas.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent report suggested that CT shows the cysts quite clearly and also allowed the localization of the affected bowel segments, thereby making CT a more sensitive and discriminating diagnostic tool. Diverticulosis, gas-containing abscess, and gas inclusions or gas layer resulting from coprostasis are potential sources of error related to the CT diagnosis of PCI (7).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the aforementioned theories seem to insufficient to explain the presence of gas in HPV in our case. However, as a matter of fact, the presence of gas in porto-mesenteric veins is assumed as idiopathic in approximately 15% of cases [7,9].…”
Section: Discussionmentioning
confidence: 99%